More than just a cut: a qualitative study of penile practices and their relationship to masculinity, sexuality and contagion and their implications for HIV prevention in Papua New Guinea - Kelly Angela; Kupul Martha; Nake Trumb Richard; Aeno Herick; Neo James; Fitzgerald Lisa; Hill Peter S; Kaldor John M; Siba Peter; Vallely Andrew (BMC, 2012)
Abstract Background Male circumcision (MC) has been shown to reduce vaginal transmission of HIV to men. While community acceptability is important in a countries preparedness to introduce MC, it is equally important to map contemporary MC and other penile cutting practices, and the socio-cultural dimensions underpinning these practices. Methods A total of 482 men and women (n = 276 and n = 210, respectively) participated in 82 semi-structured and 45 focus group discussions from four different provinces of Papua New Guinea (PNG), each representing one of the four socially and geographically diverse regions of the country. Results Of the men interviewed 131 self-reported that they had undergone a penile alteration with some reporting multiple types. Practices were diverse and could be grouped into five broad categories: traditional (customary) penile cutting; contemporary penile cutting; medical circumcision; penile inserts; and penile bloodletting practices in which sharp objects are used to incise the glans and or inserted and withdrawn from the male urethra or in order to induce bleeding. Socio-cultural traditions, enhanced sexual pleasure and improved genital hygiene were key motivators for all forms of penile practices. Conclusions The findings from this study highlight the complex and diverse nature of penile practices in PNG and their association with notions of masculinity, sexuality and contagion. Contemporary penile practices are critical to a community's acceptance of MC and of a country's ability to successfully implement MC in the context of a rich and dynamic culture of penile practices. If a MC program were to be successfully rolled out in PNG to prevent HIV it would need to work within and build upon these diverse cultural meanings and motivators for penile practices already commonly performed in PNG by men.